Respuesta :

The expression can be simplified as follows:

a. (-4)(-2) -6(2 - 5) = 26

b. 12.7 - 18.5 + 15 + 6.3 - 1 + 28.5 = 43

c. 23 - (17 - 3.4)² +  6 = -155.96

How to solve an expression using PEMDAS rule?

The expressions can be solved using PEMDAS rule,

P = Parenthesis

E = Exponential

M = Multiplication

D = division

A = addition

S = Subtraction

Hence,

a.

(-4)(-2) -6(2 - 5) = (-4)(-2) - 6(-3) = 8 + 18 = 26

b.

12.7 - 18.5 + 15 + 6.3 - 1 + 28.5 = -5.8 + 15 + 6.3 - 1 + 28.5 = 9.2 + 6.3 - 1 + 28.5 = 15.5 - 1 + 28.5 = 14.5 + 28.5 = 43

c.

23 - (17 - 3.4)² +  6 = 23 - (13.6)² + 6 = 23 - 184.96 + 6 = -161.96 + 6 = -155.96

learn more on expression here: https://brainly.com/question/1015001

#SPJ1